Simulation and Analysis of Multiphase Boost Converter with Soft-Switching for Renewable Energy Application - A. A. Bakar; M.U. Wahyu; A. Ponniran; T. Taufik (Institute of Advanced Engineering and Science, 2017)
This paper presents the simulation design of dc/dc interleaved boost converter with zero-voltage switching (ZVS). By employin the interleaved structure, the input current stresses to switching devices were reduced and this signified to a switching conduction loss reduction. All the parameters had been calculated theoretically. The proposed converter circuit was simulated by using MATLAB/Simulink and PSpice software programmes. The converter circuit model, with specifications of output power of 200 W, input voltage range from 10 60 V, and operates at 100 kHz switching frequency was simulated to validate the designed parameters. The results showed that the main switches of the model converter circuit achieved ZVS conditions during the interleaving operation. Consequently, the switching losses in the main switching devices were reduced. Thus, the proposed converter circuit model offers advantages of input current stress and switching loss reductions. Hence, based on the designed parameters and results, the converter model can be extended for hardware implementation.